2D layered crystals for thermoelectric nanocomposites and devices - Ng, Hong Kuan (2016)
The field of thermoelectrics has displayed great potentiality as one of the viable technologies for cleaner and more sustainable energy sources due to the escalating energy crisis in the 21st century. Thermoelectric (TE) devices allow waste thermal energy (heat) to be directly converted into electrical energy from heat sources via the Seebeck effect. Conversely, the Peltier effect can induce heating or cooling effects by converting electrical energy into thermal energy. The key advantages of TE devices over conventional power sources are its reliability and negligible greenhouse gas emissions. Currently, many efforts are placed into pushing its figure of merits (ZT) to greater than 3 in order for TE applications to attain wider economical applications.